2020
DOI: 10.1186/s12917-020-02567-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acupuncture for the treatment of pain associated with naturally-occurring osteoarthritis in dogs: a prospective, randomized, placebo-controlled, blinded clinical trial

Abstract: Background Acupuncture has been used as a treatment for pain associated with osteoarthritis (OA) for thousands of years; however, there is a lack of definitive evidence for this indication in humans or animals. The aim of this study was to prospectively evaluate the efficacy of acupuncture on lameness and clinical function in dogs affected by naturally-occurring OA using objective outcome measures. A total of 32 client-owned dogs completed this prospective, randomized, placebo-controlled, blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…There were no age or breed restrictions. Only patients with a score of ≥3 based on a previously described ( 27 ) Subjective Orthopedic Scoring system (SOS) grading for combined scores of “Lameness at walk” and “Lameness at trot” were included. Lameness secondary to OA could be bilateral, but one side had to be worse based on both subjective (SOS grading) and objective (%BWD) measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no age or breed restrictions. Only patients with a score of ≥3 based on a previously described ( 27 ) Subjective Orthopedic Scoring system (SOS) grading for combined scores of “Lameness at walk” and “Lameness at trot” were included. Lameness secondary to OA could be bilateral, but one side had to be worse based on both subjective (SOS grading) and objective (%BWD) measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Various outcome measures were scheduled to be collected at weeks 0, 4, 8, 12, 24, 36, and 48 of the trial (see Figure 1 ). Objective gait analysis was performed using a pressure sensitive walkway (Tekscan HR Walkway ™ 6 VersaTek System), and %BWD, defined as {[PVF (N) of the limb/total PVF (N) of all four limbs in one gait cycle] × 100}, was collected as previously described ( 27 ). Briefly, animals were evaluated at the walk or trot (based on their preference), but the velocity was kept consistent between time points.…”
Section: Methodsmentioning
confidence: 99%
“…Photobiomodulation ( 64 ) and acupuncture ( 65 ) are considered appropriate modalities to support the multimodal therapy approach based on subjective outcome measures and clinical experience of some panelists; see detailed description in appendix.…”
Section: Treatment Guidelinesmentioning
confidence: 99%
“…Extensive human studies have shown a beneficial effect of acupuncture in the treatment of OA ( 177 ), but metanalyses are not always conclusive and the claimed small analgesic effect cannot be clearly distinguished from bias ( 178 ). Veterinary studies are not different ( 65 ), in parts due to the difficulties in pain assessment and the challenges of standardizing a treatment protocol. The differentiation of electroacupuncture vs. dry needle acupuncture is one of the questions that would be interesting to have answered.…”
Section: Treatment Guidelinesmentioning
confidence: 99%
“…From a veterinary perspective, this represents a definitive recognition of animal pain and poses veterinary practitioners in an “algological position”, i.e., to play a proactive role in recognizing, assessing and managing animal pain. Indeed, many efforts have been made in this direction during the last decades and several European and US groups are moving toward the development of better protocols to detect [ 2 , 3 , 4 , 5 , 6 , 7 ], measure [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and treat [ 7 , 15 , 16 , 17 , 18 ] animal pain accordingly. The ever-increasing availability of well-designed pain scales for acute and chronic pain in dogs and cats [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and the Pain Management Guidelines [ 27 , 28 ] are good examples.…”
Section: Introductionmentioning
confidence: 99%